Interfacial carrier transport properties of a gallium nitride epilayer/quantum dot hybrid structure. Issue 4 (17th January 2022) - Wei, Huiyun; Qiu, Peng; Yu, Meina; Song, Yimeng; Li, Ye; He, Yingfeng; Peng, Mingzeng; Liu, Xiaohu; Zheng, Xinhe
Abstract : A suitable energy level arrangement is formed between GaN and CdSe QDs, and the GaN epilayer exhibits better electron extraction ability and faster interfacial electron transfer than the rutile TiO2 single crystal. Abstract : Electron transport layers (ETLs) play a key role in the electron transport properties and photovoltaic performance of solar cells. Although the existing ETLs such as TiO2, ZnO and SnO2 have been widely used to fabricate high performance solar cells, they still suffer from several inherent drawbacks such as low electron mobility and poor chemical stability. Therefore, exploring other novel and effective electron transport materials is of great importance. Gallium nitride (GaN) as an emerging candidate with excellent optoelectronic properties attracts our attention, in particular its significantly higher electron mobility and similar conduction band position to TiO2 . Here, we mainly focus on the investigation of interfacial carrier transport properties of a GaN epilayer/quantum dot hybrid structure. Benefiting from the quantum effects of QDs, suitable energy level arrangements have formed between the GaN and CdSe QDs. It is revealed that the GaN epilayer exhibits better electron extraction ability and faster interfacial electron transfer than the rutile TiO2 single crystal. Moreover, the corresponding electron transfer rates of 4.44 × 10 8 s −1 and 8.98 × 10 8 s −1 have been calculated, respectively. This work preliminarily shows the potential application of GaN in quantum dot solar cells (QDSCs). Carefully tailoring the structure and optoelectronic properties of GaN, in particular realizing the low-temperature deposition of high-quality GaN on various substrates, will significantly promote the construction of highly efficient GaN-ETL based QDSCs.